Evaluation of the acidity in the juice from different parts of the stem of sugarcane, cycle 2010/2011 - Da Silva Neto, Helio Francisco [UNESP]; Modesto Homem, Bruno Fernandes [UNESP]; Tasso Junior, Luiz Carlos [UNESP]; Omir Marques, Marcos [UNESP] (Interciencia, 2014)
The acidity levels present in the juice of sugarcane can cause problems in its processing. This study aimed to compare the values of total, volatile and fixed acidity in the juice of the stem nodes and internodes of sugarcane. The experimental design was a completely randomized, 3x2 factorial arrangement with four replications, using three varieties of sugarcane (IAC91-1099; ISC95 and CTC7-5000) divided into node and internode. The stems were collected and separated in node and internode. After extraction of juice from each part, total, volatile and fix acidities were determined. The results were subjected to variance analysis the by F test and compared by the Tukey test at 5% probability. The cultivar CTC7 had the lowest levels of total and fixed acidity. Cultivar IAC91-1099 showed high levels of fixed acidity on both parts of the stem, and high volatile acidity at the node. In the stem, the values of volatile acidity showed no definite pattern between cultivars. The node has, in general, a higher fixed acidity, but some cultivars have shown opposite results.